2020
DOI: 10.1159/000505475
|View full text |Cite
|
Sign up to set email alerts
|

Primary Idiopathic Complex Aphthosis: Diagnosis and Successful Treatment with Montelukast in a 44-Year-Old Filipino Female

Abstract: Recurrent aphthous stomatitis (RAS) is an oral condition characterized by frequent attacks of painful oral ulcers. Complex aphthosis (CA) is a severe form of RAS described as the almost constant presence of ≥3 oral ulcers with or without genital aphthosis. Management of primary CA varies, but most patients warrant the use of systemic agents. Because of prolonged treatment, it is preferred to use systemic medications with the least side effects. Herein, we present a case of a primary idiopathic CA. Workup and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…A pilot study conducted on recurrent aphthous stomatitis by Femiano et al, 2010 confirmed that montelukast induced comparable improvement compared to prednisolone; provided that montelukast has lower side effects compared to prednisolone (26). Similarly, a case study conducted by Aquino and Jamora, 2020 confirmed that montelukast improved recurrent aphthous stomatitis when patients were transferred to montelukast for 5 months (27). Because there is little research on the role of MTK in mouth ulcer healing, the primary goal of this study is to look into the effect of MTK on oral ulcer healing by looking at the histological parameters of produced oral ulcers in rats.…”
Section: Introductionmentioning
confidence: 92%
“…A pilot study conducted on recurrent aphthous stomatitis by Femiano et al, 2010 confirmed that montelukast induced comparable improvement compared to prednisolone; provided that montelukast has lower side effects compared to prednisolone (26). Similarly, a case study conducted by Aquino and Jamora, 2020 confirmed that montelukast improved recurrent aphthous stomatitis when patients were transferred to montelukast for 5 months (27). Because there is little research on the role of MTK in mouth ulcer healing, the primary goal of this study is to look into the effect of MTK on oral ulcer healing by looking at the histological parameters of produced oral ulcers in rats.…”
Section: Introductionmentioning
confidence: 92%